Animal Models of Lassa Fever - Rachel A. Sattler (Pathogens, 2020)
Lassa virus (LASV), the causative agent of Lassa fever, is estimated to be responsible for up to 300,000 new infections and 5000 deaths each year across Western Africa. The most recent 2018 and 2019 Nigerian outbreaks featured alarmingly high fatality rates of up to 25.4%. In addition to the severity and high fatality of the disease, a significant population of survivors suffer from long-term sequelae, such as sensorineural hearing loss, resulting in a huge socioeconomic burden in endemic regions. There are no Food and Drug Administration (FDA)-approved vaccines, and therapeutics remain extremely limited for Lassa fever. Development of countermeasures depends on relevant animal models that can develop a disease strongly mimicking the pathogenic features of Lassa fever in humans. The objective of this review is to evaluate the currently available animal models for LASV infection with an emphasis on their pathogenic and histologic characteristics as well as recent advances in the development of a suitable rodent model. This information may facilitate the development of an improved animal model for understanding disease pathogenesis of Lassa fever and for vaccine or antiviral testing.